Prevalence of vaccine and non-vaccine human papillomavirus types among women in Accra and Kumasi, Ghana: a cross-sectional study - Oksana Debrah; Francis Agyemang-Yeboah; Emmanuel Timmy Donkoh; Richard Harry Asmah (BMC, 2021)
Abstract Background Human Papillomavirus (HPV) infection is the main etiological factor for pre-invasive and invasive cervical cancer. HPV type-specific vaccination is being widely recommended to control the burden of disease, but the genotype-specific distribution of HPV may vary in different countries. The aim of the study was to determine the prevalence and distribution of HPV genotypes among women attending reproductive health services in Ghana, their associated risk factors, and to assess the potential coverage of identified HPV genotypes by three licensed vaccines among these women. Method Women presenting for reproductive health services in two regional hospitals in Accra and Kumasi from October 2014 to March 2015 were conveniently recruited into the study (n = 317). HPV-DNA detection and genotype identification were carried out by a nested multiplex PCR assay that combines degenerate E6/E7 consensus primers and type-specific primers for the detection and typing of eighteen HPV genotypes. Cytology was performed to screen women for cervical cancer lesions. Risk factors for HPV infection were analyzed by logistic regression. Statistical significance was accepted for p < 0.05. Results The age of study participants ranged from 21 to 76 years. Among women positive for HPV, 35.0% were infected with high-risk HPV, 14.5% with probable high-risk HPV, and 17.0% with low-risk HPV. The prevalence of HPV 16/18 was 8.2%, HPV 6/11/16/18 was 9.1% and HPV 6/11/16/18/31/33/45/52/58 was 28.4%. The most prevalent among HR-HPV were types 52 (18.3%) and 58 (8.8%). HPV positivity may be associated with educational background (p < 0.001), age at first pregnancy (p = 0.028), and age at coitarche (p = 0.016). Conclusions Our study revealed a high prevalence of HR-HPV infection among women. The high prevalence of HR HPV indicates that multivalent vaccines will be useful for controlling HPV burden in general population contexts. The distribution of HPVs in this population suggests that of the three currently available vaccines the nonavalent vaccine, which protects against seven HPV types in addition to HPV 16 and 18, has the highest coverage of HPV infections among Ghanaian women. Healthcare officials planning to reduce the transmission of HPV and cervical cancer must consider the coverage of the nonavalent vaccine as an advantage.